Clemente's anatomy dissector : guides to individual dissections in human anatomy with brief relevant clinical notes (applicable for most curricula) - 280640 Clemente, Carmine D. (Philadelphia: Wolters Kluwer/Lippincott Williams & Wilkins, 2010)
Includes bibliographical references and index